2003
DOI: 10.1053/jlts.2003.50233
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus therapy, hepatocyte drug metabolism, and risk for acute cellular rejection

Abstract: We recently reported on a series of patients who experienced acute cellular rejection (ACR) during the treatment of hepatitis C virus (HCV) infection in our posttransplantation cohort. Our hypothesis is that HCV clearance improves hepatic microsomal function, which in turn results in lower trough cyclosporine (CyA) and tacrolimus (TAC) levels, predisposing the patient to ACR. Records of all patients receiving transplants for HCV infection at our center from 1993 to June 2002 were reviewed. Two hundred three pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 21 publications
2
55
1
Order By: Relevance
“…Conversely, a higher incidence of AR and CR has been observed in HCV-positive patients compared with those transplanted for other disease [77][78][79][80][81]. This association probably reflects a number of factors -these include different approaches to immunosuppression in HCV-positive patients, shared pathways of immune-mediated damage between HCV and rejection and the effects of anti-viral therapy, which may result both in non-specific augmentation of the host's immune system and increased hepatocellular metabolism of immunosuppressive drugs following viral clearance from hepatocytes [81][82][83].…”
Section: Hepatitis C and Rejectionmentioning
confidence: 99%
“…Conversely, a higher incidence of AR and CR has been observed in HCV-positive patients compared with those transplanted for other disease [77][78][79][80][81]. This association probably reflects a number of factors -these include different approaches to immunosuppression in HCV-positive patients, shared pathways of immune-mediated damage between HCV and rejection and the effects of anti-viral therapy, which may result both in non-specific augmentation of the host's immune system and increased hepatocellular metabolism of immunosuppressive drugs following viral clearance from hepatocytes [81][82][83].…”
Section: Hepatitis C and Rejectionmentioning
confidence: 99%
“…Close monitoring of calcineurin inhibitor levels are necessary during antiviral therapy. A greater proportion of responders to antiviral therapy experience rejection than nonresponders, presumably because improved hepatic function leads to enhanced biotransformation and lower immunosuppression levels [38].…”
Section: Risk Of Rejection With Interferonmentioning
confidence: 99%
“…Chronic rejection led to retransplantation in three cases. Moreover, several cases of acute cellular rejection have been reported during antiviral therapy in patients with hepatitis C [41,42]. A recent report suggests that HCV clearance during treatment might predispose to acute cellular rejection by improving hepatic microsomal function (and thereby decreasing levels of cycosporine or tacrolimus) [42].…”
Section: Treatment Of Chronic Hepatitis After Ltmentioning
confidence: 99%
“…Moreover, several cases of acute cellular rejection have been reported during antiviral therapy in patients with hepatitis C [41,42]. A recent report suggests that HCV clearance during treatment might predispose to acute cellular rejection by improving hepatic microsomal function (and thereby decreasing levels of cycosporine or tacrolimus) [42]. Controlled studies have not confirmed an association between interferon therapy and acute cellular or chronic rejection [43], but this might be explained by the relatively small size of the published series.…”
Section: Treatment Of Chronic Hepatitis After Ltmentioning
confidence: 99%